THE ROLE OF GIS IN ADDRESSING ENVIRONMENTAL, SOCIAL AND TOURISTIC CHALLENGES IN MOHAMMEDIA CITY, MOROCCO - M. R. Simou; H. Rhinane; M. Maanan (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
During the last years, Morocco’s Environmental, Social and Touristic perspectives has improved significantly, but it remains one of the biggest challenges for Mohammedia city. The purpose of this study is to locate an optimal site for the construction of a new Waste Water Treatment Plant (WWTP) in order to help the environment, to select an appropriate site for the construction of a new School that will benefit the social needs of the city and to create a suitable tour plan of touristic sites for tourism. It was carried out by using Geographic Information System (GIS), Remote Sensing (RS), Global Positioning System (GPS) devices, Digital cameras and Multi- criteria Decision Analysis (MCDA).Throughout the process, the used data for both WWTP and School selection include the remote sensing data of multi spectral satellite imageries and the digital elevation model combined with vector data of land use (LU) layers, and for Tour creation the used data include collected photographs and GPS data from the site. According to MCDA, the results presents an optimal site with an area of 48283,02 m2 for a new WWTP, a suitable area with an area of 3200 m² for a new School and a city tour for tourists with a distance of 27 km.